The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1002/(sici)1097-4652(199610)169:1<78::aid-jcp8>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Rat lung alveolar type II cell line maintains sodium transport characteristics of primary culture

Abstract: Culture of primary alveolar type II cells has been widely used to investigate the Na+ transport characteristics of alveolar epithelium. However, this model was restricted by early morphological and physiological dedifferentiation in culture. Recently, a cell line has been obtained by transfection of neonatal type II cells with the simian virus SV40 large T antigen gene (SV40-T2). SV40-T2 cells have retained proliferative characteristics of the primary type II cells (Clement et al., 1991, Exp. Cell Res., 196:19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Simian virus 40 (SV40)-transformed strain AT2 neonatal alveolar epithelial cells were used for the in vitro internalization assays (4). SV40-AT2 cells retain the sodium transport properties of alveolar type II cells and express RTI 40 (rat alveolar epithelial type I cell protein; molecular mass, approximately 40 kDa) (25,31). SV40-AT2 cells were grown in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% heat-inactivated fetal calf serum (FCS) (Labtech International, East Sussex, United Kingdom), penicillin (100 U/ml), and streptomycin sulfate (100 g/ml) (Invitrogen, Paisley, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…Simian virus 40 (SV40)-transformed strain AT2 neonatal alveolar epithelial cells were used for the in vitro internalization assays (4). SV40-AT2 cells retain the sodium transport properties of alveolar type II cells and express RTI 40 (rat alveolar epithelial type I cell protein; molecular mass, approximately 40 kDa) (25,31). SV40-AT2 cells were grown in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% heat-inactivated fetal calf serum (FCS) (Labtech International, East Sussex, United Kingdom), penicillin (100 U/ml), and streptomycin sulfate (100 g/ml) (Invitrogen, Paisley, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…The alveolar type II cell is responsible for the secretion of surfactant (65, 66) as well as vectorial transport of sodium from the apical to the basolateral surface (67,132,214,216,217,228,238). The active transport of sodium by type II cells appears to provide a major driving force for removal of fluid from the alveolar space.…”
Section: A Structural Features Of the Distal Pulmonary Epitheliamentioning
confidence: 99%
“…In situ hybridization studies, as well as Northern blot analyses done in mice, rats, and humans, have identified the presence of mRNA for all three subunits of ENaC in alveolar epithelial type II cells both in vivo and in vitro with usually a greater expression of ␣-than ␤-and ␥-subunits (64,75,78,162,220,223,232,238,264,315,345,348). The relative amounts of ENaC mRNA could explain the difference in ENaC activity and amiloride sensitivity between tissues and species, although a direct relationship between mRNA and functional protein cannot be predicted.…”
Section: Amiloride-sensitive Sodium Channels and Enacmentioning
confidence: 99%
“…Previously, it was thought that the AT2 cell is responsible for the majority of the vectorial transport of Na ϩ across the alveolar epithelial barrier (56,68,109,110,114,123,154). However, recently, an important role for AT1 cell in vectorial Na ϩ transport has been demonstrated, and it appears that the ␣ 2 Na-K-ATPase isozyme expressed mostly in AT1 cells is responsible for ϳ60% of Na ϩ transport (23, 89,154,155).…”
Section: Alveolar Epitheliummentioning
confidence: 99%